Temporalities of care in networked learning: A sociomaterial study of post-pandemic LMS practices in Indonesia - Rahman, Ahmad Ardillah; Oliver, Martin (Proceedings of the International Conference on Networked Learning, 2026)
Learning Management Systems (LMS) have become an integral part of teaching in Indonesian higher education, extending beyond their emergency role during the Covid-19 pandemic. Through the national SPADA initiative (Sistem Pembelajaran Daring Indonesia, or Indonesian Online Learning System), the government mandates universities to use the platform as part of everyday teaching and learning practices. This move not only redefines how learning and teaching are experienced by teachers and students but also entangles new temporal pressure and fragmentation shaping the enactment of care. Drawing on Sharma’s (2014) concept of chronopolitics and Tronto’s (1993) ethics of care informed by a sociomaterial perspective, this study investigates how lecturers enact care across temporal and digital structures in post-pandemic Indonesian higher education. It specifically explores how the technological entanglements reconfigure lecturers’ temporal rhythms, educational care relations and labour dynamics as they adapt to institutional demands of LMS use. This study employs a qualitative, participatory methodology combining photovoice and semi-structured interviews with ten lecturers teaching in different universities across Indonesia who actively used LMS platforms. Participants generated photographs that matter to them, depicting workspaces, tools (digital and non-digital), and humans or non-humans that they felt represented their practices teaching with LMS platforms. The photographs were used as prompts during interviews. Reflexive thematic analysis was employed to interpret the data. Findings suggest that LMS platforms rehape how learning takes place and transform teaching into distributed and fragmented networks. While LMS are designed to simplify teaching, they paradoxically generate new forms of invisible care work, intensifying lecturers’ temporal pressures through monitoring and surveillance, and prompting performative behaviours to ensure their labour is recognised. Lecturers develop ‘radical’ strategies of resistance and self-care, such as delegating administrative tasks, enlisting surrogate labour, or setting strict boundaries on availability, to reclaim temporal control within the temporal architecture of LMS platforms. This paper contributes to sociomaterial and care scholarship by showing how the chronopolitics of digital infrastructures redistribute temporal power, reconfigure educational relations, and shape the enactment of care in networked learning. It argues that sustaining care in networked higher education requires recognising these hidden temporal burdens and reimagining institutional practices that value the embodied, emotional, and material dimensions of academic work.